Problems of Online Learning During Pandemic - arjunina maqbulin (Balai Diklat Keagamaan Surabaya, 2021)
Since the present of Corona virus, all aspects of human live are changed. This also happened in education field. Because of this pandemic, students have to do online learning. They can not go to school for the healthy problem reason. This research aimed to find the answer of two research questions. The first is about the students’ problem in having online learning during the pandemic, and the second is the students point of view about the platform used in online learning. The data were collected from the students of MAN 2 Nganjuk, academic year 2020/2021. The method of research used is qualitative. Questionnaire was used to collect the data. Descriptive analysis was used to analyze the data. The result of this research revealed that the main problem faced by students in having online learning during the pandemic is in understanding the material, this problem is agreed by 59% of the respondent. Then, 23% of the respondent complained about many tasks that they have to finish. Further more 10% of the students think that they have problem in economy field about the quota. The next problem faced by the students of MAN 2 Nganjuk is about time, 6% of the respondents complain about this, and 2% of the participants complain about the way to send their task. The next result of this research is students point of view about the platform used in online learning. According to them the favorable platform to be used in online learning, the first is google classroom, this platform is loved by 52% of the respondents. Then, 39% of the respondents choose whatsapp, those are two most favorable platform loved by the students to be used in teaching learning process during the pandemic. In addition these two platforms are also the platforms that are mostly used by teachers in delivering the materials. For teaching learning process during the pandemic time, it is suggested that teachers give more motivation to the students so that they can become active learners and learn from any sources.